Using food loss reduction to reach food security and environmental objectives–a search for promising leverage points - Kuiper, Marijke; Cui, Hao David (Elsevier, 2021)
We identify promising leverage points for food loss reductions from a food system perspective with a global economy-wide model capturing price and income feedbacks of changes at different points in the supply chain. Using new FAO food loss estimates we model loss reduction as a zero-cost productivity increase at primary and processing stages, simultaneously deriving the response of food security (national availability, accessibility and utilisation of food) and sustainability indicators (GHG emissions, agricultural land use) at global and regional levels. To help focus data collection and intervention efforts we identify interventions by region, supply chain stage and sector contributing most to improving nutrition and sustainability. While the loss rates show no clear relation to regional income, strongest impacts on food security and environment are in low income regions. Decomposing indicator responses to the exogenous loss reduction shocks we find a focus on domestic primary stages achieving strong and unambiguous positive impacts on both food security and environment. Since foreign loss reductions may harm food insecure agricultural households through import substitution, the most food insecure countries should be part of any global loss reduction efforts. Fruit and vegetables and animal products are found to have the strongest impact on both food security and environment. A marginal impact on GHG emissions remains once non-agricultural expansion following the productivity increase is accounted for, showing the importance of an economy-wide perspective.